Ryzyko jako element kształtowania struktury kapitałowej przedsiębiorstwa - Szczęsna-Urbaniak, Agnieszka (Risk as a Determinant of Capital Structure, 2005)
This article concerns the problems of the internal risk of a company. The right estimation of risk is an indispensable condition of correct estimation of cash flows of incomes and expenses connected with realisation of examined investment-projects and the right qualification of present net values of these undertakings. The process of taking rational decision aims to achieve equilibrium between of the return on the employed capital and the level of risk. Using of provides a company performance based only on owner's equity is not sufficient. Capital taken from outside usually is necessary. In many cases the outside capital is indispensable to run an enterprise successful. In addition this capital enhance the profitability of domestic one and gives the effect called as leverage. That is why the right capital structure is essential for efficiency of every company performance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 424-434